Synergistic Effect of Sugarcane Bagasse and Zinc Oxide Nanoparticles on Eco-Remediation of Cadmium-Contaminated Saline Soils in Wheat Cultivation - Emad M. Hafez; Khadiga Alharbi; Hany S. Gharib; Alaa El-Dein Omara; Essam Elatafi; Maha M. Hamada; Emadelden Rashwan; Tarek Alshaal (Plants)
Soil contamination with cadmium (Cd) and salinity poses a significant challenge, affecting crop health and productivity. This study explores the combined application of sugarcane bagasse (SCB) and zinc oxide nanoparticles (ZnO NPs) to mitigate the toxic effects of Cd and salinity in wheat plants. Field experiments conducted in Cd-contaminated saline soils revealed that the application of SCB (0, 5, and 10 t ha−1) and ZnO NPs (0, 12.5, and 25 mg L−1) significantly improved key soil physicochemical properties, including soil pH, electrical conductivity (EC), and exchangeable sodium percentage (ESP). The combined application of SCB and ZnO NPs significantly mitigated the effects of Cd and salinity on soil and wheat plants. SCB (10 t ha−1) reduced soil pH by 6.2% and ESP by 30.8% compared to the control, while increasing microbial biomass by 151.1%. ZnO NPs (25 mg L−1) reduced Cd accumulation in wheat shoots by 43.3% and seeds by 46.3%, while SCB and ZnO NPs combined achieved a reduction of 74.1% and 62.9%, respectively. These amendments enhanced antioxidant enzyme activity, with catalase (CAT) increasing by 35.3% and ascorbate peroxidase (APX) by 54.9%. Wheat grain yield increased by 42% with SCB alone and by 75.2% with combined SCB and ZnO NP treatment, underscoring their potential as eco-friendly soil amendments for saline, Cd-contaminated soils. These results underscore the potential of SCB and ZnO NPs as eco-friendly amendments for improving wheat productivity in contaminated soils, offering a promising strategy for sustainable agriculture in salt-affected areas.